DAMPAK APLIKASI HERBISIDA IPA GLIFOSAT DALAM SISTEM TANPA OLAH TANAH (TOT) TERHADAP TANAH DAN TANAMAN PADI SAWAH - S. Dharma Kesuma; - Hariyadi; Syaiful Anwar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2015)
Weed is one of the important constraints in rice production, and therefore its effective control measure should be considered that the production can be optimized. The application of no tillage by using herbicide is assumed more effective and efficient than conventional one. However, herbicide which is used as contionusly can influence residue in soil, plant and rice. The objectives of the research were to analyze the effect of no tillage and its combination of IPA glyphosate herbicide concentration levels to rice productivity and to analyze IPA glyphosate herbicide residue in soil, straw and rice. The study was conducted in the field by using IPA glyphosate herbicide with five treatments, namely maximum tillage (Gm), no herbicide spraying (G0), glyphosate herbicide doses 1.5 l ha-1(G1), 3 l ha-1 (G2) and 4.5 l ha-1(G3). The analysis of glyphosate residue was done in soil, straw and rice samples by using HPLC (high performance liquid chromatography) method. The research results showed that Gm and G1 treatments had highest with rice yield average were 938 g m-2 and 728 g m-2, respectively. Gm treatmen more profitable with R / C ratio of 1.84 with a profit of Rp 13.714 million, but using more labor than G1 treatment. Thereby, no-tillage treatment (G1) could be done by using glyphosate herbicide in doses 1.5 l ha-1, economically. Glyphosate contained in soil samples, straw, and rice proved that using of gyphosate intensively could have negative impacts on soil microbial activity, plant resistance to plant diseases and residue of glyphosate carried by plants. Glyphosate residue concentration was highest found on rice sample in treatments G3 was 0.272 mg kg-1. These glyphosate residual values on rice was highest than maximum residue limit which was decided by Indonesia government (0.1 mg kg-1). Glyphosate residues contained in food is not within safe limits if taken every day and can cause adverse effects to human health. Keywords: glyphosate herbicide, maximum residue limits, paddy field, weed control